Timber reinforcement in reinforced concrete beam for light structure - Nurul Jannah, Mohamad (2014)
Many researches and development of new reinforcement material for concrete structure as an alternative to the existing reinforcement material which is steel have been done nowadays. Timber looked like another alternative which possesses high strength ratio compare to its weight even basically; its strength is incompatible to steel. This study's focus on the flexural behaviour of beam reinforced with timber and also to make a comparison between the laboratory test and theory applying the Reinforced Concrete Design to EC2. In the result of flexural test, it showed that control beam which named STEEL carried the utmost loads compared to sample beam which reinforced with Balau and Meranti timber. Both of them are named as BALAU and MERANTI. Compared to the flexural strength of STEEL beam which is 73.18 kN, BALAU beam reached 69 % of the value meanwhile MERANTI is 66 % respectively. In comparison of deflection, BALAU beam reached 68 % of the control beam's value, which is convenient with the difference of flexural strength. For MERANTI, it showed the large different with only 26 % and it is not compatible with the value of flexural strength. This condition happened because of the stiffness of reinforcement. For the failure mode of the beam, it is closely related to the loaddeflection behaviour. The larger the load-deflection value, the wider the range of cracking. Based on comparison of theoretical and experimental result, it can be concluded that the theoretical value of ultimate moment resistance is higher compared to experimental. This study concluded that, the Balau timber has a possibility to be an alternative to replace the steel in reinforced concrete structures because from the result of testing, the value is quite competitive compared to steel reinforcement.